2017
DOI: 10.3390/nu9080845
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Evaluation of Lactobacillus delbrueckii subsp. bulgaricus KLDS1.0207 for the Alleviative Effect on Lead Toxicity

Abstract: Lead (Pb) is a toxic contaminating heavy metal that can cause a variety of hazardous effects to both humans and animals. In the present study, Lactobacillus delbrueckii subsp. bulgaricus KLDS1.0207 (L. bulgaricus KLDS1.0207), which has a remarkable Pb binding capacity and Pb tolerance, was selected for further study. It was observed that the thermodynamic and kinetic model of L. bulgaricus KLDS1.0207 Pb binding respectively fit with the Langmuir–Freundlich model and the pseudo second-order kinetic model. Scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 45 publications
4
37
0
Order By: Relevance
“…Similarly, Bhakta et al (36) proved ability of six isolated from Pediococcus dextrinicus and Pediococcus acidilactici to tolerance, high concentration of Pb <1000, for all isolated, where's the MIC value for a Cd range from 50 to 250 for the six isolates. Li et al (37) reported that the MIC value for Pb by L. bulgaricus KLDS10207 was >1000. Since the bacteria under study showed high tolerance for both Pb and Cd, so they were used in the study of removing of these two metals using different concentration 25 and 50 ppm, and during 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Bhakta et al (36) proved ability of six isolated from Pediococcus dextrinicus and Pediococcus acidilactici to tolerance, high concentration of Pb <1000, for all isolated, where's the MIC value for a Cd range from 50 to 250 for the six isolates. Li et al (37) reported that the MIC value for Pb by L. bulgaricus KLDS10207 was >1000. Since the bacteria under study showed high tolerance for both Pb and Cd, so they were used in the study of removing of these two metals using different concentration 25 and 50 ppm, and during 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of seven KLDS strains to bind the Pb was investigated as formerly described by Li et al (2017) , with little amendments. Incubation of all strains was carried out for 16 h, and the centrifugation of the cultivated biomass was done at 10,000 g for 10 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The kidney and liver tissues were split into 5 μm thickness with rotary microtome and fixed in paraffin. These sliced tissues were stained with hematoxylin-eosin and then observed by light microscopy ( Li et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we identified a series of wild L. bulgaricus strains preserved by the Dairy Industrial Culture Collection, Key Lab of Dairy Science, Ministry of Education, China. These strains were obtained from Chinese traditional fermented dairy products, and they exhibited excellent flavor, viscosity, postacidification production characteristics, and key enzyme expression features (Liu et al, 2013;Hou et al, 2015;Li et al, 2017). However, their bacteriophage-resistance capacities have not been studied before.…”
Section: Introductionmentioning
confidence: 99%